(untitled) (Fiep Bulletin - online, 2013)
Both physical and mental health conditions, relevant factors in the conception of quality of life, are correlated with selfesteem. This study evaluated the association between physical health and self-esteem to understand whether changes in the levels of fatigue, energy, and pain are associated with self-esteem. This cross-sectional descriptive study enrolled a convenience sample of 997 individuals living in the Vale dos Sinos, southern Brazil. Physical health was analyzed using the WHOQOL-100 physical domain, and self-esteem, the Rosenberg self-esteem scale. The Spearman correlation coefficient (p=0.05) and the SPSS 15.0 software were used for data analysis. Results showed that people that had frequent physical pain agreed that they did not have much to be proud of ( = -0.180). Participants that were satisfied with their level of energy were also satisfied with themselves. ( = -0.309). Those that were unhappy about their sleep also felt that they were failures ( = 0.207). The only QoL facet not associated with self-esteem was pain and discomfort. The analysis of results showed that there is an important correlation between physical health and self-esteem, and points to the importance of a multiple dimension approach to healthcare because different factors are closely interconnected in the perception of self image.